2020
DOI: 10.1016/j.rbmo.2019.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Testicular tissue cryopreservation is the preferred method to preserve spermatogonial stem cells prior to transplantation

Abstract: Onofre completed his training in Human Reproduction and ART at the Biomedical Sciences faculty of the University Paris Diderot and later his PhD in Medical Sciences at the Vrije Universiteit Brussel in the optimization and safety of fertility preservation strategies to avoid and cure male infertility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…We believe that these insights will have potential translational value in the development of fertility restoration strategies for childhood cancer survivors. Cryopreservation of ITT is a preferred method over isolated spermatogonial stem cells banking [24]. Handling of ITT prior to cryopreservation or in vitro culture may influence testicular architecture, endocrine function, and spermatogonial proliferation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We believe that these insights will have potential translational value in the development of fertility restoration strategies for childhood cancer survivors. Cryopreservation of ITT is a preferred method over isolated spermatogonial stem cells banking [24]. Handling of ITT prior to cryopreservation or in vitro culture may influence testicular architecture, endocrine function, and spermatogonial proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Cryopreservation of ITT is a preferred method over isolated spermatogonial stem cells banking [ 24 ]. Handling of ITT prior to cryopreservation or in vitro culture may influence testicular architecture, endocrine function, and spermatogonial proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Reliable cryopreservation methods also ensure the optimal protection of the reproductive potential by maintaining the health of SSCs within the biopsy [16]. Research has shown that the cryopreservation of the testicular biopsy tissue as a piece is preferable to the cryopreservation of the testicular cell suspension after dissociation of the biopsy as the viability of SSCs is better preserved in testicular biopsies [6]. Biopsy cryopreservation protocols do not only safeguard the viability, longevity, and proliferation rate of the SSCs but also increase their fecundity rate.…”
Section: Testis Biopsy and Cryopreservationmentioning
confidence: 99%
“…Nonetheless, before SSCT, an aliquot of the cell suspension after propagation is recommended for safety testing (e.g. infectious contamination) [6]. This step could also include a safety check for the presence of original cancer cells [25] or resorting for leukemic cells in order to increase the purity of the SSCs [27].…”
Section: Eliminating Infiltrated Cancer Cells From the Biopsymentioning
confidence: 99%
See 1 more Smart Citation